Expression of human cathelicidin peptide LL‐37 in inflammatory bowel disease. (28th September 2017) - Kusaka, S.; Nishida, A.; Takahashi, K.; Bamba, S.; Yasui, H.; Kawahara, M.; Inatomi, O.; Sugimoto, M.; Andoh, A.
Summary: Cathelicidin peptide LL‐37 plays an important role in the early host response against invading pathogens via its broad‐spectrum anti‐microbial activity. In this study, we investigated LL‐37 expression in the inflamed mucosa of inflammatory bowel disease (IBD) patients. Furthermore, the regulatory mechanism of LL‐37 induction was investigated in human colonic subepithelial myofibroblasts (SEMFs). LL‐37 mRNA expression and protein secretion were analysed using real‐time polymerase chain reaction and enzyme‐linked immunosorbent assay, respectively. Intracellular signalling pathways were analysed using immunoblotting and specific small interference RNA (siRNA). The expression of LL‐37 mRNA was increased significantly in the inflamed mucosa of ulcerative colitis and Crohn's disease. The Toll‐like receptor (TLR)‐3 ligand, polyinosinic‐polycytidylic acid (poly(I:C), induced LL‐37 mRNA expression and stimulated LL‐37 secretion in colonic SEMFs. The transfection of siRNAs specific for intracellular signalling proteins [Toll/IL‐1R domain‐containing adaptor‐inducing interferon (IFN) (TRIF), tumour necrosis factor receptor‐associated factor (TRAF)6, transforming growth factor β‐activated kinase (TAK)1] suppressed the poly(I:C)‐induced LL‐37 mRNA expression significantly. Poly(I:C)‐induced phosphorylation of mitogen‐activated protein kinases (MAPKs) and activated nuclear factor kappa B (NF‐κB) and activating factor protein (AP)‐1. siRNAs specific for NF‐κB and c‐Jun inhibited poly(I:C)‐induced LL‐37 mRNA expression. LL‐37 suppressed lipopolysaccharide (LPS)‐induced interleukin (IL)‐6 and IL‐8 expression significantly in colonic SEMFs. The expression of LL‐37 was up‐regulated in the inflamed mucosa of IBD patients. LL‐37 was induced by TLR‐3 stimulation and exhibited an anti‐microbial effect via interaction with lipopolysaccharide (LPS). Abstract : Cathelicidin peptide LL‐37 plays an important role in the early host response against invading pathogens via its broad‐spectrum antimicrobial activity. The expression of LL‐37 was upregulated in the inflamed mucosa of IBD patients. LL‐37 was induced by TLR3 stimulation and exhibited an anti‐microbial effect via interaction with LPS.